2022
DOI: 10.1088/1755-1315/1085/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Relocation rationale – why people move in connection with renovation projects

Abstract: The existing housing stock is constantly in need of maintenance and renovation. Previous research has showed that renovation projects may force tenants to move involuntarily, and there is a correlation between the scale of the renovation project, the economic consequences for the tenants, and the relocation frequency. In this paper, the aim is to identify the reasons for tenants’ choice to relocate, based on both quantitative and qualitative data. This paper is based on material from a larger study of tenants’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…regarding the choice of new kitchen tiles) increased feelings of control, self-efficacy, empowerment, ownership and pride, improving mental health, confirming pathways 3 and 6 [ 15 ] and findings from Bal et al [ 33 ] and Allen [ 34 ]. Similar to our study, Granath et al [ 35 ] found respondents had negative emotions connected to the renovation and relocation process, e.g. worries about the (lack of) information before the renovation started, or not wanting to live through a renovation in their present apartment, and that “the renovation project in itself, with the disturbances and stresses it brings, are a large cause for people to move” ([ 35 ], p.5).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…regarding the choice of new kitchen tiles) increased feelings of control, self-efficacy, empowerment, ownership and pride, improving mental health, confirming pathways 3 and 6 [ 15 ] and findings from Bal et al [ 33 ] and Allen [ 34 ]. Similar to our study, Granath et al [ 35 ] found respondents had negative emotions connected to the renovation and relocation process, e.g. worries about the (lack of) information before the renovation started, or not wanting to live through a renovation in their present apartment, and that “the renovation project in itself, with the disturbances and stresses it brings, are a large cause for people to move” ([ 35 ], p.5).…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our study, Granath et al [ 35 ] found respondents had negative emotions connected to the renovation and relocation process, e.g. worries about the (lack of) information before the renovation started, or not wanting to live through a renovation in their present apartment, and that “the renovation project in itself, with the disturbances and stresses it brings, are a large cause for people to move” ([ 35 ], p.5). Our findings further indicated that after renovation, mental health might improve due to improved housing quality and visual amenity benefits, which decrease stress about housing problems and increase feelings of pride, confirming pathway 2 [ 15 ] and findings from Orlando-Romero et al [ 36 ] highlighting the psychosocial component of people’s relationship with their house.…”
Section: Discussionsupporting
confidence: 93%
“…The dataset for the text classification task is based on empirical data collected in a larger study of tenants’ experiences with housing renovation and their decisions to move from their homes (n = 447). 41 The study was conducted in Gothenburg, Sweden, during the period of 2018 and 2021. In the above-mentioned study, researchers interviewed tenants who agreed to participate in the study and then transcribed the interviews to text to be further analysed and coded into different categories.…”
Section: Methodsmentioning
confidence: 99%